THE CONSTITUTION OF THE KINGDOM OF THAILAND 2017 AND THE CRIMINAL JUSTICE REFORM - Suriyo (Khongkhawai), Phrakhruwinaithon Suriya; Sinprasitkul, Wichet (Journal of Buddhist Anthropology, 2021)
The problems of the justice system in Thailand greatly affect the faith crisis in the justice system. When law enforcement has many drawbacks Since the investigation and the use of various measures Before bringing it to the court hearing As a result, the Thai criminal justice system has long - standing problems, affecting the trust of people and abroad. That is to say, there are many obstacles and shortcomings. Especially in the charging process. Criminal prosecution investigation Especially the separate problem of the investigation with the litigation work such flaws, as a result, The enactment of the Constitution of the Kingdom of Thailand, B.E. 2560 (2017), is the first constitution with a section on judicial reform. And focus on the class of prosecution Which is the duty of the police and the prosecutor in the investigation of truth which is at the heart of the justice process. And affect people in their rights, liberties, human rights, human dignity, and the rule of law Working together in both parties, the Truth of First Justice investigation is fairly jointly investigated in this area. Countries using the Code and Common Law system in the prosecution investigation, collaboration must be done independently of the police and the prosecutor. And there is a management that prevents external interference. Corruption in the investigation Throughout the law, personnel administration of the police, and appropriate prosecutors. Therefore, investigation reform was suggested by allowing joint prosecution investigations. By adjusting the prosecutor's responsibility to investigate the police from the outset. And adjust the personnel management of the police investigation line to be independent in work according to the guidelines of the Constitution of the Kingdom of Thailand B.E. 2560